Outcomes of induction of labour in women with previous caesarean delivery: a retrospective cohort study using a population database. - Sarah J Stock; Evelyn Ferguson; Andrew Duffy; Ian Ford; James Chalmers; Jane E Norman (PLoS ONE)
Background There is evidence that induction of labour (IOL) around term reduces perinatal mortality and caesarean delivery rates when compared to expectant management of pregnancy (allowing the pregnancy to continue to await spontaneous labour or definitive indication for delivery). However, it is not clear whether IOL in women with a previous caesarean section confers the same benefits. The aim of this study was to describe outcomes of IOL at 39-41 weeks in women with one previous caesarean delivery and to compare outcomes of IOL or planned caesarean delivery to those of expectant management. Methods and findings We performed a population-based retrospective cohort study of singleton births greater than 39 weeks gestation, in women with one previous caesarean delivery, in Scotland, UK 1981-2007 (n = 46,176). Outcomes included mode of delivery, perinatal mortality, neonatal unit admission, postpartum hemorrhage and uterine rupture. 40.1% (2,969/7,401) of women who underwent IOL 39-41 weeks were ultimately delivered by caesarean. When compared to expectant management IOL was associated with lower odds of caesarean delivery (adjusted odds ratio [AOR] after IOL at 39 weeks of 0.81 [95% CI 0.71-0.91]). There was no significant effect on the odds of perinatal mortality but greater odds of neonatal unit admission (AOR after IOL at 39 weeks of 1.29 [95% CI 1.08-1.55]). In contrast, when compared with expectant management, elective repeat caesarean delivery was associated with lower perinatal mortality (AOR after planned caesarean at 39 weeks of 0.23 [95% CI 0.07-0.75]) and, depending on gestation, the same or lower neonatal unit admission (AOR after planned caesarean at 39 weeks of 0.98 [0.90-1.07] at 40 weeks of 1.08 [0.94-1.23] and at 41 weeks of 0.77 [0.60-1.00]). Conclusions A more liberal policy of IOL in women with previous caesarean delivery may reduce repeat caesarean delivery, but increases the risks of neonatal complications.